Wi-Fi Robotic Vacuum Cleaner and Air Purifier With Automatic/Manual Control Operation: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
AbstractIn cities all around the world, air pollution is a major issue that is typically brought on byparticulate matter, such as dust, smoke, pollen, bacteria, etc. The problem is that some ofthese are able to get inside our homes, especially if we live in a large city. The Wi-Fi RoboticVacuum Cleaner and Air Purifier with Automatic/Manual Control Operation is a two-in-onedevice, a vacuum cleaner, and an air purifier integrated with sensors for effective functionality.It sucks in small particles of dry dirt on smooth floor surfaces and purifies air against fine andharmful particles in the air.The results of functional testing for the components and sensors used in the prototype showedthe in-depth details of the prototype’s design, program, and electric circuit connection. Thetesting showed that the obstacle sensors, gas sensors, and fine dust sensors serve theirfunctions. The filters on the vacuum and air purifier also showed physical evidence of catchingsmall particles, which supports the fact that the prototype is able to collect small particles ofdirt both on the floor and in the air.By means of prototype testing and data analysis, the researchers found out that moving an airpurifier together with a vacuum cleaner gives us the ideal robot for indoor hygiene, improvingnot only the air quality but also removing dust from the floor. The robot is also portable andeasy to control for manual navigation.
Keywords: Computer Science & Engineering